Deep-Sea Echinoid Trails and Seafloor Nutrient Distribution: Present and Past Implications. - Miguez-Salas, Olmo; Vardaro, Michael F.; Rodríguez-Tovar, Francisco J.; Pérez-Claros, Juan Antonio; Huffard, Christine L. (Frontiers Media, 2022)
The movement patterns of deep-sea bioturbational fauna are believed to be the result of the organism’s interactive response to the perceived spatial distribution of nutritional resources on the seafloor. To address this hypothesis, we examined the movement paths of Echinocrepis rostrata -a common epibenthic bioturbator echinoid in the northeast Pacific Ocean- through fractal analysis in order to characterize how they cover the seafloor during foraging. We used an 18-yr time series photographic record from 4100-m depth at an abyssal site in the eastern North Pacific (Sta. M; 34°50′N, 123°00′W; 4100 m depth). Echinocrepis rostrata paths showed low fractal values (1.09 to 1.39). No positive correlation between particulate organic carbon (POC) flux measured from sediment traps at 600 m and 50 m above bottom and fractal dimension (FD) values was observed. The movement of echinoids was characterized by high-speed periods, followed by slower speed periods and higher turning rates. These slow-speed periods were correlated with higher sinuosity values, slightly wider turning angles, and numerous cross-cuts. Based on visual estimation of seafloor phytodetritus coverage, we hypothesize that its small-scale distribution may be the primary determinant of echinoid feeding movement patterns rather than the bulk amount of nutrients. Finally, this finding reveals new insights into the morphological studies of trace fossils, indicating that trails of past echinoid trace makers could help to evaluate nutrient availability/distribution in the ancient deep-sea and help to decipher past climate-induced changes.
Keywords: Equinoideos; Invertebrados fósiles; Ecología abisal; Paleontología; Graphoglyptid trace fossils; Time-series; Abyssal site; NE Pacific; Bioturbation; Climate station; Matter; Ocean